IMPLIKASI PERLINDUNGAN INDIKASI GEOGRAFIS BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 TERHADAP PENGEMBANGAN EKONOMI LOKAL - Sudjana, Sudjana (Veritas et Justitia, 2018)
This study discusses, on the basis of analysis of Law No. 20 of 2016, the potential impact of Geographical Indication protection to local economy. By tracing other relevant laws and regulations, using in depth analysis of existing literature and other relevant qualitative data on the subject matter, the author argues that: (1) Law No. 20 of 2016 compared to the Law it replaces it more sufficient to provide protection and legal certainty to Geographical Indication beneficiaries; (2) Quite a number of potential Geographical Indications exist in Indonesia which deserve protection, especially in relation to its potential to support local economic development.